Digitality, Rhetoric, and Protocological Fascism; Or, Fascist Ants & Democratic Cicadas. Issue 1 (2nd January 2020) - Pfister, Damien Smith
ABSTRACT: Myths about pharmaka are especially useful during dramatic cultural and technical changes. This essay first explores a contemporary myth, Bernard Stiegler's "Allegory of the Anthill, " as a warning about protocological fascism – the industrialized and undemocratic exercise of control through digital infrastructures. Following Stiegler, I suggest that the algorithms structuring many digital technologies threaten to impose ant-like efficiency logics on subjects, making them more susceptible to the homogenizing political impulses of fascism. If not the logos of the ant, what should we aspire to? To answer this question, I turn to the myth of the cicadas in Plato's Phaedrus . Lysias, Socrates' antithesis in the Phaedrus, is associated with an ant-like practical rhetoric that prizes industry over virtue. Opposed to the ant's efficiency logics is the cicada, associated with poetic world-making, joy, and mania . I argue that the cicada might be recuperated as an icon of democratic renewal, resonance, resistance, and re-enchantment.